INJECTION MOLDING OF STRUCTURED MULTIPHASE MATERIALS - A B Semenov; A N Muranov; A A Kutsbakh; B I Semenov (RUDN Journal of Engineering Research, 2017)
Contemporary and future-oriented mechanical engineering requires the use of a new set of methods for processing, manufacturing, changing the state of materials implemented in the production process. In particular, the level of modern and prospective blank part production industries is largely related to the development of injection molding of structured multiphase materials - powder and granule technologies of a new generation. In this article, such widely used by foreign industry modern injection molding technologies of structured multiphase materials as the powder injection molding (PIM) technology and the thixoforming technology, are considered. A description of specific rheological effects that determined the fundamental possibility of the appearance and practical application of these technologies is given, and some of the most relevant physico-mathematical models of rheological behavior of structured multiphase materials are considered. In addition, the article demonstrates the efficiency of implementation and high potential for development of powder injection molding technology (PIM) for mass production of small-sized shaped parts in Russian Federation. The need for the development of educational programs and standards, including special disciplines and courses aimed at training technical professionals not only in the field of present commonly used technologies, but also such promising technologies as powder injection molding (PIM) and thixoforming, was noted as w